Evaluation of cytotoxicity levels of poly vinyl ether silicone, polyether, and poly vinyl siloxane impression materials: An in vitro study - Rajasimhan, N; Jayaraman, Srinivasan; Ali, Doulathunnisa; Subramanian, Balanehru (The journal of Indian Prosthodontic Society, 2019)
Aim: To assess the cytotoxicity level of newly introduced poly vinyl ether silicone (PVES) compared to poly vinyl siloxane (PVS) and polyether (PE) elastomeric impression materials. Settings and Design: Comparative -Invitro study design. Materials and Methods: Mouse cell line NIH/3T3 was grown in Dulbecco's modified Eagle's medium. Samples of three elastomers were dissolved in dimethyl sulfoxide and were tested at various concentrations. Twenty-four well plates with NIH/3T3 cells with different concentrations of elastomeric solutions were incubated at 37°C. 3-(4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide assay was performed on day 1, 3, and 7, with a time interval of 15 min, 30 min, 60 min, and 24th h to estimate the cytotoxicity for all three elastomers. Statistical Analysis Used: Kruskal-Wallis ANOVA test and the period effect within the subjects, repeated-measure ANOVA was done using the Greenhouse-Geisser correction method. Results: The mean cell viability (survival rate) of NIH 3T3 cells at the concentrations tested was measured. A repeated-measure Kruskal-Wallis ANOVA determined the mean survival concentration on day 1, 3, and 7. PVES showed significant decrease in the survival rate on day 1 than PVS and PE, while PVS and PE had significant decrease in the survival rates of cells on day 3 and 7 which were statistically significant (P < 0.001). Conclusion: PVES shows early cytotoxic signs as compared to PVS and PE, and cell viability for PVS was the highest among all. When making impression with PVES and PE, it is always better to evaluate the impression and gingival sulcus carefully with magnification to prevent adverse reaction, if any material is left inadvertently for longer period of time.